PKB/SGK-Resistant GSK-3 Signaling Following Unilateral Ureteral Obstruction - Jakob Voelkl; Sobuj Mia; Adrian Meissner; Mohamed S. Ahmed; Martina Feger; Bernat Elvira; Britta Walker; Dario R. Alessi; Ioana Alesutan; Florian Lang (Karger Publishers, 2014)
Background/Aims: Renal tissue fibrosis contributes to the development of end-stage renal disease. Causes for renal tissue fibrosis include obstructive nephropathy. The development of renal fibrosis following unilateral ureteral obstruction (UUO) is blunted in gene-targeted mice lacking functional serum- and glucocorticoid-inducible kinase SGK1. Similar to Akt isoforms, SGK1 phosphorylates and thus inactivates glycogen synthase kinase GSK-3. The present study explored whether PKB/SGK-dependent phoshorylation of GSK-3α/β impacts on pro-fibrotic signaling following UUO. Methods: UUO was induced in mice carrying a PKB/SGK-resistant GSK-3α/β (gsk-3KI) and corresponding wild-type mice (gsk-3WT). Three days after the obstructive injury, expression of fibrosis markers in kidney tissues was analyzed by quantitative RT-PCR and western blotting. Results: GSK-3α and GSK-3β phosphorylation was absent in both, the non-obstructed and the obstructed kidney tissues from gsk-3KI mice but was increased by UUO in kidney tissues from gsk-3WT mice. Expression of α-smooth muscle actin, type I collagen and type III collagen in the non-obstructed kidney tissues was not significantly different between gsk-3KI mice and gsk-3WT mice but was significantly less increased in the obstructed kidney tissues from gsk-3KI mice than from gsk-3WT mice. After UUO treatment, renal β-catenin protein abundance and renal expression of the β-catenin sensitive genes: c-Myc, Dkk1, Twist and Lef1 were again significantly less increased in kidney tissues from gsk-3KI mice than from gsk-3WT mice. Conclusions: PKB/SGK-dependent phosphorylation of glycogen synthase kinase GSK-3 contributes to the pro-fibrotic signaling leading to renal tissue fibrosis in obstructive nephropathy.